2015
DOI: 10.7205/milmed-d-14-00504
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Performance is Not Degraded After Stellate Ganglion Block Treatment for Post-Traumatic Stress Disorder: A Case Series

Abstract: In this case series of 11 patients, SGB effectively treated PTSD symptoms and did not impair reaction time, memory, or concentration. Therefore, SGB should be considered as a viable treatment option for personnel with PTSD symptoms who will be placed in demanding conditions such as combat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The secondary literature search identified an additional 7 publications resulting in 32 publications included in the review. These comprised 15 case reports and case series, 1 systematic case review, 2 publications related to a single published RCT, and 14 nonsystematic reviews, opinions, guidelines, commentaries, books, and book chapters . The systematic search results are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary literature search identified an additional 7 publications resulting in 32 publications included in the review. These comprised 15 case reports and case series, 1 systematic case review, 2 publications related to a single published RCT, and 14 nonsystematic reviews, opinions, guidelines, commentaries, books, and book chapters . The systematic search results are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…A further case series in 2015 among military service members diagnosed with PTSD evaluated effects of SGB on measures of neurocognitive performance, including memory and reaction time, and found no impairment in these functional categories with treatment. The authors concluded these findings constituted a potential advantage of SGB, particularly for military service members who might return to combat . Bringing further synthesis to the expanding literature base, Lipov and Ritchie published a new review, and Lipov published an extensive book chapter discussing the potential for SGB to serve as an alternative treatment option for combat‐related PTSD …”
Section: Resultsmentioning
confidence: 99%
“…The pathogenesis of chronic ulcerative colitis is complex. However, recent studies have shown that this disease and immune dysfunction are correlated[ 41 , 42 ], and that the stellate ganglion block technique plays a very important role in regulating immune function[ 43 - 46 ]. Therefore, the main aim of this study was to investigate the efficacy and safety of the stellate ganglion block technique in the treatment of chronic ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…4 Specific for this indication, the SGB procedure has been evaluated in 14 peer-reviewed publications since 1990, including a multicenter randomized clinical trial in 2019, supporting this modality's safety and effectiveness in the successful treatment of PTSD symptoms across a variety of patient demographics and trauma etiologies. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Though 1 small trial showed the effects of SGB were equivalent to a sham injection, it should be noted that the SGB arm in this study still demonstrated an 8-point reduction in PTSD checklist (PCL) scores at 1 month. 16 While many of these early studies are level 2 or 3 evidence, a collective examination of all studies demonstrates consistent findings with respect to safety, onset of relief, magnitude of effect, and success rates.…”
Section: Original Researchmentioning
confidence: 98%